Elementary Math Learning Design: An Integration with Islamic Environmental Ethics in the First Grade - Luluk Mauluah; Marsigit Marsigit; Muhammad Nur Wangid (TARBIYA: Journal of Education in Muslim Society, 2020)
AbstractThis research discusses the design of mathematics learning based on   Islamic Environmental Ethics (IEE). The purpose of the research was to discover how to implement IEE in elementary mathematics learning, especially grade 1. This qualitative research method begins with the analysis of condition grade1 to 6. By analyzing the themes of grade 1 to grade 6, then themes are qualified percentage according to the use of terms related to Islamic Environmental Ethics (IEE) and after that,  compiled a matrix containing competencies, classes, activities and assessments to implement it. The results of this study are, the first year has the lowest percentage of 32.5 % of its IEE content so it needs to be developed. From the selection of basic competencies, 3.5, 4.5, 3.6 and 4.6 are selected for their implementation. The implications obtained by the IEE component concerning Islamic concern for the earth, especially those listed in the hadith on cleanliness. Based on the hadith, learning activities are arranged using used goods at worksheet one and worksheet 2. Based on its activities, assessment is prepared through rubrics, performance assessments and questionnaires.                                                                      Abstrak     Penelitian ini membahas tentang desain pembelajaran matematika berbasis Islamic Environmental Ethics (IEE). Tujuan dari penelitian ini adalah untuk mengetahui bagaimana penerapan IEE pada pembelajaran matematika SD khususnya kelas 1. Metode penelitian kualitatif ini diawali dengan analisis kondisi kelas 1 sampai dengan kelas 6. Dengan menganalisis tema dari kelas 1 sampai dengan kelas 6, maka tema tersebut memenuhi syarat. persentase sesuai penggunaan istilah terkait Islamic Environmental Ethics (IEE) dan setelah itu disusun matriks yang berisi kompetensi, kelas, kegiatan dan penilaian untuk mengimplementasikannya. Hasil dari penelitian ini, tahun pertama memiliki persentase terendah yaitu 32,5% konten IEE-nya sehingga perlu dikembangkan. Dari pemilihan kompetensi dasar tersebut dipilih 3.5, 4.5, 3.6 dan 4.6 untuk pelaksanaannya. Implikasi yang diperoleh komponen IEE tentang kepedulian Islam terhadap bumi, terutama yang tercantum dalam hadits tentang kebersihan. Berdasarkan hadits, kegiatan pembelajaran disusun dengan menggunakan barang bekas pada LKS satu dan LKS dua. Berdasarkan kegiatannya disusun penilaian melalui rubrik, penilaian kinerja dan angket.How to Cite:  Mauluah, L., Marsigit, Wangid, M. N. (2020).  Elementary Math Learning Design: An  Integration with Islamic Environmental Ethics in the First Grade. TARBIYA: Journal of Education in Muslim Society, 7(2), 241-251. doi:10.15408/tjems.v7i2.19975.